Entropy Analysis of Temperature Swing Adsorption for CO2 Capture Using the Computational Fluid Dynamics (CFD) Method - Zhihao Guo; Shuai Deng; Shuangjun Li; Yahui Lian; Li Zhao; Xiangzhou Yuan (Entropy, 2019)
Carbon capture by adsorption is supposed to be an effective method to reduce CO2 emissions, among which Temperature Swing Adsorption (TSA) can utilize low-grade thermal energy even from renewable energy source. At present, TSA technology still has several challenges to be practical application, such as intensive energy-consumption and low energy-efficiency. Thermodynamics could be a powerful method to explore the energy conversion mechanism of TSA, among which entropy analysis could further provide a clear picture on the irreversible loss, even with a possible strategy of energy-efficient improvement. Based on the theory of non-equilibrium thermodynamics, the entropy analysis of TSA cycle is conducted, using the Computational Fluid Dynamics (CFD) method. The physical model and conservation equations are established and calculation methods for entropy generation are presented as well. The entropy generation of each process in cycle is analyzed, and the influence from the main parameters of desorption process is presented with optimization analysis. Finally, the performance of the cycle with regeneration is compared with that of the cycle without regeneration, and the method of reducing the entropy generation is obtained as well. This paper provides possible directions of performance improvement of TSA cycle with regards on energy utilization efficiency and the reduction of irreversible loss.